Genome-wide identification of antisense lncRNAs and their association with susceptibility to Flavobacterium psychrophilum in rainbow trout - Ali, Ali; Salem, Mohamed (Frontiers in Immunology, 2022)
Eukaryotic genomes encode long noncoding natural antisense transcripts (lncNATs) that have been increasingly recognized as regulatory members of gene expression. Recently, we identified a few antisense transcripts correlating in expression with immune-related genes. However, a systematic genome-wide analysis of lncNATs in rainbow trout is lacking. This study used 134 RNA-Seq datasets from five different projects to identify antisense transcripts. A total of 13,503 lncNATs were identified genome-wide. About 75% of lncNATs showed multiple exons compared to 36.5% of the intergenic lncRNAs. RNA-Seq datasets from resistant, control, and susceptible rainbow trout genetic lines with significant differences in survival rate following Flavobacterium psychrophilum (Fp) infection were analyzed to investigate the potential role of the lncNATs during infection. Twenty-four pairwise comparisons between the different genetic lines, infectious status, and time points revealed 581 differentially expressed (DE) lncNATs and 179 differentially used exons (DUEs). Most of the DE lncNATs strongly and positively correlated in expression with their corresponding sense transcripts across 24 RNA-Seq datasets. LncNATs complementary to genes related to immunity, muscle contraction, proteolysis, and iron/ heme metabolism were DE following infection. LncNATs complementary to hemolysis-related genes were DE in the resistant fish compared to susceptible fish on day 5 post-infection, suggesting enhanced clearance of free hemoglobin (Hb) and heme and erythropoiesis. LncNATs complementary to hepcidin, a master negative regulator of the plasma iron concentration, were the most downregulated lncNATs on day 5 of bacterial infection in the resistant fish. Ninety-four DE lncNAT, including five complementary to hepcidin, are located within 26 QTL regions previously identified in association with bacterial cold water disease (BCWD) in rainbow trout. Collectively, lncNATs are involved in the molecular architecture of fish immunity and should be further investigated for potential applications in genomic selection and genetic manipulation in aquaculture.